Implementasi Kurikulum Berbasis Cinta dalam Membentuk Karakter Humanis Peserta Didik Madrasah Ibtidaiyah - A.A. Az-Zabaniiyah Muailah (AJER: Advanced Journal of Education and Religion, 2026)
This study aims to describe the implementation of the Love-Based Curriculum and the role of teachers in developing love values ​​in students at Darul Ulum Elementary School, Dumpiagung Kembangbahu, Lamongan. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation. Research informants included the principal, class teachers, and educators directly involved in the learning process. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the Love-Based Curriculum at MI Darul Ulum has been carried out contextually through the stages of planning, implementation, and evaluation of learning. The values ​​of love are integrated into learning objectives, teacher-student interactions, humanistic learning methods, and classroom management that prioritizes compassion, empathy, and a persuasive approach. The values ​​of love developed include compassion, empathy, tolerance, social awareness, and mutual respect. The role of teachers in the implementation of the Love-Based Curriculum is very significant, namely as designers of value-based learning, facilitators of humanistic learning, role models in daily behavior, and evaluators who assess students' academic development and character continuously. Supporting factors for curriculum implementation include teacher commitment, a religious and humanistic school culture, support from the principal, and a conducive social environment. Inhibiting factors include differences in teachers' understanding of the Love-Based Curriculum concept, limited infrastructure, teachers' administrative burden, and the absence of standard technical guidelines. This study confirms that the Love-Based Curriculum can be implemented effectively through learning practices and school culture even though it has not been formalized in a specific curriculum document.